Cost-Benefit Analysis of Vaccination Strategies to Prevent Mother-to-Child Transmission of the Hepatitis B Virus Using a Markov Model Decision Tree - Nan Yang; Lei Lei; Yiyu Meng; Naitong Zhou; Lizheng Shi; Ming Hu (Frontiers Media S.A., 2022)
ObjectivesCurrently, in China, several strategies exist to prevent mother-to-child transmission (MTCT) of the hepatitis B virus (HBV). These include providing Hepatitis B vaccination and hepatitis B immunoglobulin (HBIG) injection with different types of administration and dosages. The aim of this study is threefold: first, to evaluate the economic viability of current hepatitis B vaccination strategies for preventing MTCT from a public health policy perspective; second, to optimize the current immunization strategy for preventing perinatal transmission of the HBV; and third, to offer policy options to the National Health Commission in China.MethodsTo simulate the disease outcome for the entire life of newborns infected with HBV, a Markov model with eight possible health states was built by using TreeAge Pro 2011 software. In the present study, the model parameters were probability and cost, which were extracted from literature and calculated using Microsoft Excel 2013. The optimal immunization strategies were identified through cost-benefit analyses. A benefit-cost ratio (BCR) > 1 indicated that the strategy had positive benefits and vice versa. A one-way sensitivity analysis was used to investigate the stability of the results.ResultsFrom a public health care system perspective, we evaluated the economic viability of 11 strategies in China. For all 11 strategies, the BCR was > 1, which indicated that the benefits of all the strategies were greater than the costs. We recommended strategy number 9 as being optimal. In strategy number 9, babies born to hepatitis B surface antigen (HBsAg)-positive mothers were given an HBIG (200 IU) within 24 h of birth and three injections of hepatitis -B vaccine (20-μg each) at 0, 1, and 6 months, and the strategy had a BCR of 4.61. The one-way sensitivity analysis revealed that the full vaccination coverage and effective rates of protection were two factors that greatly influenced the BCR of the different prevention strategies; other factors had little effect.ConclusionThe benefits of all strategies were greater than the costs. For decision-making and application, the strategy should be based on local socio-economic conditions so that an appropriate immunization strategy can be selected.